Potassium Channel Conductance Is Involved in Phenylephrine-Induced Spontaneous Firing of Serotonergic Neurons in the Dorsal Raphe Nucleus - Wang, Jing; Wang, Yingzi; Du, Xiaona; Zhang, Hailin (Frontiers in Cellular Neuroscience, 2022)
The serotonergic network from the dorsal raphe nucleus (DRN) of the brain has been demonstrated to regulate behaviours including learning, cognition, emotion and sleep-wake cycle. Dysregulation of the activity of serotonergic neurons in the DRN is thought to play an important role in emotional disorders. Activity of serotonergic neurons is regulated by norepinephrine (NE) released from the projection terminals of the noradrenergic input from the locus coeruleus (LC), through activation of α1-adrenoceptor. However, insight into the molecular mechanism for this NE-indued regulation of serotonergic neuron activity is not clear. We in this study, using agonist of α1-adrenoceptor phenylephrine (PE), methods of brain slices and patch-clamp technique, found that the A-type, the KCNQ, and the calcium-activated small-conductance K+ channels (SK) are the targeted K+ channels of PE action which underlies the PE-induced spontaneous firing in the DRN serotonergic neurons. By using single-cell PCR and immunofluorescence methods, we also identified the isoform members of these K channel families which may contribute to the NE/PE-induced spontaneous firing of the DRN serotonergic neurons.